The quality criteria of the school texts of communication of the V cycle - Laiza Cruz, Maricela (2019)
In this article we will evaluate the quality of the school text of primary communication of the V cycle, these texts are provided by the MINEDU, in order to demonstrate the partial fulfillment of the quality indicators and the implications that it has for the achievement of the learning.